Status of Rumex palustris (Polygonaceae) in the flora of Iran: an overview of current taxonomy, anatomy and ecology - Khorasani, Mina; Naqinezhad, Alireza (Phytotaxa, 2023)
Rumex palustris (Polygonaceae) is recorded as a new taxon for the flora of Iran. The species was firstly collected from the seasonal wet dune slacks on south Caspian Sea coast, northern Iran. A full morphological description, the anatomical details of stem and leaf, along with illustrations and a distribution map are provided. Moreover, the species is morphologically and anatomically compared with R. dentatus and R. maritimus. The salient features are compared with those of related species and discussed.